Communication between Human Dendritic Cell Subsets in Tuberculosis: Requirements for Naive CD4+ T Cell Stimulation - Lozza, Laura; Farinacci, Maura; Bechtle, Marina; Stäber, Manuela; Zedler, Ulrike; Baiocchini, Andrea; del Nonno, Franca; Kaufmann, Stefan H. E. (Frontiers in Immunology, 2014)
Human primary dendritic cells (DCs) are heterogeneous by phenotype, function and tissue localization and distinct from inflammatory monocyte-derived DCs. Current information regarding the susceptibility and functional role of primary human DC subsets to Mycobacterium tuberculosis (Mtb) infection is limited. Here, we dissect the response of different primary DC subsets to Mtb infection. Myeloid CD11c+ cells and pDCs (C-type lectin 4C+ cells) were located in human lymph nodes (LNs) of tuberculosis (TB) patients by histochemistry. Rare CD141hi DCs (C-type lectin 9A+ cells) were also identified. Infection with live Mtb revealed a higher responsiveness of myeloid CD1c+ DCs compared to CD141hi DCs and pDCs. CD1c+ DCs produced interleukin (IL)-6, tumor necrosis factor α and IL-1β but not IL-12p70, a cytokine important for Th1 activation and host defenses against Mtb. Yet, CD1c+ DCs were able to activate autologous naïve CD4+ T cells. By combining cell purification with fluorescence-activated cell sorting and gene expression profiling on rare cell populations, we detected in responding CD4+ T cells, genes related to effector-cytolytic functions and transcription factors associated with Th1, Th17 and Treg polarization, suggesting multifunctional properties in our experimental conditions. Finally, immunohistologic analyses revealed contact between CD11c+ cells and pDCs in LNs of TB patients and in vitro data suggest that cooperation between Mtb-infected CD1c+ DCs and pDCs favors stimulation of CD4+ T cells.